Pengaruh kepemimpinan transformasional dan kompleksitas tugas terhadap kinerja pegawai dengan motivasi sebagai variabel intervening - Afriani Afriani; Andriyansyah Andriyansyah; Muji Gunarto (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
Abstract. The research aims to analyze and determine the effect of transformational leadership and task complexity on performance and the effect of transformational leadership and task complexity on employee performance mediated by motivation on employee performance mediated by motivation. Research is descriptive quantitative type. The population is all employees at the SFR Class I Bandung Monitoring Center, consisting of 40 individuals, consisting of 34 individual civil servants (excluding the Head of UPT) and 6 administrative PPNPN persons using total sampling. The analysis used is PLS-SEM (Partial Least Square Structural Equation Model). The results of the analysis show that there is a positive effect of Transformational Leadership on Performance and is statistically significant. There is a negative effect of Task Complexity on Performance but not significant. There is a positive influence of Transformational Leadership on Performance which is mediated by Motivation and is not significant. There is a negative effect of Task Complexity on Performance which is mediated by Motivation and is not statistically significant Keywords: Transformational leadership; Employee Performance; Task Complexity; Motivation Abstrak. Riset bertujuan menganalisa serta mengetahui pengaruh kepemimpinan transformasional, dan kompleksitas tugas terhadap kinerja serta pengaruh kepemimpinan transformasional dan kompleksitas tugas terhadap kinerja pegawai yang diperantarai oleh motivasi terhadap kinerja pegawai yang dimediasi oleh motivasi. Riset berjenis kuantitatif deskriptif. Populasi ialah seluruh pegawai di Balai Monitor SFR Kelas I Bandung sebanyak 40 individu, terdiri atas 34 individu PNS (tidak termasuk Kepala UPT) dan 6 orang PPNPN administrasi menggunakan total sampling. Analisa yang dipakai ialah PLS-SEM (Partial Least Square Structural Equation Model). Hasil analisis terdapat pengaruh positif Kepemimpinan Transformasional pada Kinerja dan secara statistik signifikan. Terdapat pengaruh negatif Kompleksitas Tugas terhadap Kinerja namun tidak signifikan. Adanya pengaruh positif Kepemimpinan Transformasional pada Kinerja yang dimediasi oleh Motivasi dan tidak signifikan. Terdapat pengaruh negatif Kompleksitas Tugas pada Kinerja yang dimediasi oleh Motivasi dan secara statistik tidak signifikan. Katakunci: Kepemimpinan Transformasional; Kinerja Pegawai; Kompleksitas Tugas; Motivasi